To kill or cure - Gregory, Susanna, 1958- (London : Sphere, 2007)
Cambridge University is in dire financial straits--the town's landlords are demanding an extortionate rent rise for the students' hostels and the plague years have left the colleges with scant resources. Tension between town and gown is at a boiling point and soon explodes into violence and death. Into this maelstrom comes a charismatic physician whose healing methods owe more to magic than medicine--but his success threatens Matthew Bartholomew's professional reputation, and his life.
Keywords: Bartholomew, Matthew (Fictitious character) -- Fiction; Physicians -- Fiction; Cambridge (England) -- Fiction; Great Britain -- History -- Edward III, 1327-1377 -- Fiction; Mystery fiction